Expanding Horizons for Abdominal Aortic Aneurysms - Rolph, Rachel C.; Waltham, Matthew; Smith, Alberto; Kuivaniemi, Helena (AORTA, 2015)
Recent technological advances have allowed researchers to interrogate the genetic basis of abdominal aortic aneurysms in great detail. The results from these studies are expected to transform our understanding of this complex disease with both multiple genetic and environmental risk factors. Clinicians need to keep abreast of these genetic findings and understand the implications for their practice. Patients will become increasingly informed on genetic risk, and a new era of individualized risk assessment for AAA is just beginning. This brief update aims to provide the clinician with a succinct précis of the recent progress in this area.
Keywords: Genetic; Association Studies; Risk score; Aneurysm; DNA Sequencing